Health risks associated with group package tour: implications from a study on tour leaders in Taiwan. Issue 11 (2nd November 2022) - Lan, Fan-Yun; Tseng, Yen-Cheng; Su, Shih-Bin; Wu, Chen-Long; Guo, How-Ran
ABSTRACT: Group package tour (GPT) is more popular among Asia than in other regions. To visit multiple attractions with a group of people within limited time at low costs, GPT is associated with some potential health hazards, including restricted meal time and long periods of time on ground transportation. Tour leaders are a good target for assessing the associated health outcomes, and we conducted a questionnaire survey on tour leaders in Taiwan. In addition to 152 tour leaders, we recruited office staff of tour agencies as references. Tour leaders were more likely to have peptic ulcer/gastritis, gastroesophageal reflux disease, and lower back pain. The risks of these conditions increased as working on the job longer, indicating a causal relationship. The results suggest that restricted meal time and long periods of time travelling on ground transportation vehicles are potential health hazards associated with GPT and may lead to certain health outcomes.